Backstepping based non-linear control for maximum power point tracking in photovoltaic system. (1st January 2018) - Naghmash,; Armghan, Hammad; Ahmad, Iftikhar; Armghan, Ammar; Khan, Saud; Arsalan, Muhammad
Highlights: Backstepping based non-linear controller for MPPT of PV array has been proposed. Using Lyapunov Stability Theory, its asymptotic stability has been proved. Tracking of maximum power from the PV array has been assured. The comparison is done with Perturb & Observe method and Fuzzy Logic controller. Abstract: The increasing energy demands, depleting fossil fuels and increasing global warming due to carbon emission has arisen the need for an alternate, overall efficient and environment-friendly energy system. Solar energy is considered to be one of the most promising alternative energy sources, but it has the problem of low efficiency due to varying environmental conditions. To increase its efficiency, a maximum power point tracking (MPPT) algorithm is required to harvest maximum power from the Photovoltaic (PV) array. In this paper, a non-linear backstepping controller is proposed to extract the maximum power from the PV system. A non-inverting buck-boost converter is used as an interface between the load and the PV array. Reference voltages for the controller are generated by a regression plane. Asymptotic stability of the system is verified through Lyapunov stability analysis. The performance of the proposed controller is tested under MATLAB/Simulink platform. The simulation results validate that the proposed controller offers fast and accurate tracking. Comparison with perturb & observe and fuzzy logic controller is provided to show the performance of the proposed controller under abrupt variation of the environmental conditions.